Jewish Terrorism in Israel - Pedahzur, Ami and Perliger, Arie (New York Columbia University Press, 2009)
Ami Pedahzur and Arie Perliger propose a theory of violence that contextualizes not only recent acts of terror but also instances of terrorism that stretch back centuries. Beginning with ancient Palestine and its encounters with Jewish terrorism, the authors analyze the social, political, and cultural factors that sponsor extreme violence, proving religious terrorism is not the fault of one faith but flourishes within any counterculture that adheres to a totalistic ideology."--Jacket.
includes Illustrations, Notes and Index.
Keywords: Terrorism -- Violence--Political Aspects -- Israel